Compartment syndrome due to liquid extravasation in a pediatric patient. Case report and bibliographic review - Rueda Mojica, Juan Sebastián (2021)
Extravasation Compartment Syndrome (SCE) is an infrequent pathology, with an incidence of 0,01-6,5%, whom 1,8-11% are children. Communication in children is usually difficult, with high risk of development of SCE. A case about a 9 month old male patient with an over-infected viral pneumonia and a triggered SCE is presented. He received compartmental decompression of right forearm and right hand; however he presented mild sequelae. Treatment of extravasation injury is not always sufficient enough. Mild-to-moderate complications or SCE can be presented. Recognizing clinical manifestations and risk factors and the use of auxiliary studies is fundamental for a good diagnosis and as prevention in children. Faciotomies, gold standard for treatment, are not completely safe, and have an impact on morbidity. Early protocols against extravasation, early examination by surgeon and investigation about SCE in chil-dren are recommended.